An enhanced tree based key management scheme for secure communication of wireless sensory network - Rasul, Khadija; Nuerie, Nujhat (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.